Challenging conventional wisdom : smallholder perceptons and experience of land access and tenure security in the cotton belt of northern Mozambique - Strasberg, Paul J.; Kloeck-Jenson, Scott (Land Tenure Center, University of Wisconsin-Madison, 2002)
A new land law went into effect in January 1998 in Mozambique. The impetus behind these actions was the belief that a new legal and regulatory framework was necessary to reduce the frequency of land conflicts between largeholders and smallholders while simultaneously promoting much-needed investment in the agricultural sector. With empirical evidence presented in this report, based on smallholder survey data collected from 1994 to 1996, we challenge widely held beliefs about land tenure and access in the smallholder sector in Mozambique. Although the new land law may improve tenure security for smallholders who experience conflicts with largeholders, two key areas of policy concern have been neglected. First, while provisions in the new legal framework to safeguard local community land-use rights vis-à-vis outsiders are important, they will not be sufficient to eliminate and/or adjudicate land conflicts between smallholders themselves. Second, while much attention has been devoted to the legal and regulatory component of land tenure in Mozambique, research results reveal significant variation in the size of household landholdings even when controlling for household size. Further, land access was found to be closely linked to key welfare indicators such as income and calorie availability; a weak nonfarm economy heightens the importance of land for the welfare of rural families. These results are surprising and contradict views held by many in the policy community in Mozambique that land access is unconstrained for smallholders.
xii, 58 p.
Keywords: Farms, Small Mozambique; Land use, Rural Mozambique; Land use, Rural Government policy Mozambique; Farms, Size of Mozambique; Tenure security (Natural resources) Mozambique; Agrarian structure Mozambique; Land conflicts Mozambique